Minutes of 76th meeting of BRAC University campus development committee - Brac University (Brac University, 2023)
The 76th meeting of BRAC University Campus Development Committee (CDC) was held on November 07, 2016 with Professor Syeed Saad Andaleeb,Ph.D, Vice Chancellor of BRAC University in the chair. The chair welcomed all participants and commenced the business of the meeting.